The long-run relationship between interest rates and inflation: some cross-country evidence - Matti Virén (Bank of Finland, 1989)
This paper analyzes the effect of anticipated inflation on nominal interest rates, paying special attention to the stability of this relationship over various regimes. These regimes are analyzed to find out whether the inflation forecastability proposition recently advanced by Barsky explains the observed poor performance of the Fisher equation with historical data. The analyses make use of the so-called threshold and digression models and data from 11 western countries for 1875 - 1984. The main result of this paper is that the forecastability proposition does not explain the weakness of the anticipated inflation effect on interest rates. Rather, various institutional factors seem to be of more importance.
URN:NBN:fi:bof-201807301769
Keywords: 330